A Novel QAM Technique for High Order QAM Signaling - Ozen, Ali (Společnost pro radioelektronické inženýrství, 2011)
The paper proposes a novel spread quadrature amplitude modulation (S-QAM) technique with high SNR improvement for high-order QAM channels. Simulated and experimental bit error rate (BER) performance analyses of the proposed technique in blind and non-blind equalizers are obtained by using single carrier (SC) WiMAX (IEEE 802.16-2004) radio. Instead of using any one particular type of channel profile, this study concentrates on true frequency selective Rayleigh fading channels in the real-time WiMAX radio environment around 3.5 GHz. The Constant Modulus Algorithm (CMA) blind equalizer has been compared with the popular non-blind equalizers, Recursive Least Squares (RLS) and Least Mean Squares (LMS) algorithm, as benchmarks. It has been proven in experimental and simulated channels that CMA blind equalizer, using the proposed technique, can be considered as a low complexity, spectrum efficient and high performance time domain equalizations to be embedded in a transceiver for the next generation communications. Furthermore the proposed technique has also reduced approximately till 5 dB and 7.5 dB performance differences between non-blind and blind equalizers for 16-QAM and 64-QAM, respectively. The simulation results have demonstrated that the simulated and experimental studies of the proposed technique are compatible with each other and extremely satisfying.
Keywords: Experimental BER; adaptive blind training; WiMAX (IEEE 802.16-2004); constant modulus algorithm; S-QAM